Growth, digestive and absorptive abilities and antioxidative capacity in the hepatopancreas and intestine of young grass carp (Ctenopharyngodon idellus Val.) fed graded levels of dietary manganese. (1st December 2014) - Tang, Ren‐Jun; Feng, Lin; Jiang, Wei‐Dan; Liu, Yang; Kuang, Sheng‐Yao; Jiang, Jun; Zhang, Yong‐An; Tang, Ling; Zhou, Xiao‐Qiu
Abstract: To study the effects of manganese on growth performance, digestive and absorptive abilities, as well as the antioxidative capacity in the hepatopancreas and intestine, young grass carp ( Ctenopharyngodon idellus Val.) (264 ± 1 g) were fed diets containing graded levels of manganese at 3.65 (control), 8.62, 13.48, 18.24, 22.97 and 27.86 mg kg −1 diet for 8 weeks. Per cent weight gain (PWG) and feed intake were the poorest in fish fed the basal diet ( P < 0.05). The activities of trypsin, lipase and alkaline phosphatase in the intestine were significantly enhanced with dietary manganese level at 13.48 mg kg −1 diet ( P < 0.05). Additionally, in the hepatopancreas and intestine, the protein carbonyl and malondialdehyde contents were the lowest in fish fed the diet with dietary manganese level at 13.48 mg kg −1 diet ( P < 0.05), while the anti‐hydroxyl radical capacities, manganese superoxide dismutase (MnSOD), glutathione peroxidase and glutathione‐ S ‐transferase activities were significantly enhanced with dietary manganese level at 13.48 mg kg −1 diet ( P < 0.05). Moreover, the catalase activity and glutathione content in the intestine were the highest in fish fed the diet with dietary manganese level at 18.24 mg kg −1 diet ( P < 0.05). These results indicated that optimum dietary manganese promoted growth, enhanced the digestive and absorptive abilities, and improved the antioxidative capacity in young grass carp. Based on the quadratic regression analysis for PWG and intestinal MnSOD activity, the manganese requirements for young grass carp with the initial body weight of 264 g were 16.91 and 18.21 mg kg −1 diet respectively.